2021
DOI: 10.1002/jbt.22725
|View full text |Cite
|
Sign up to set email alerts
|

Potential effect of adrenomedullin on metabolic and endocrinal dysfunctions in the experimentally induced polycystic ovary: Targeting implication of endoplasmic reticulum stress

Abstract: This study investigated the potential effect of adrenomedullin (ADM) on metabolic and endocrinal dysfunctions in experimentally induced polycystic ovary. Twenty‐four female Wistar rats were allocated into three groups: control; polycystic ovary syndrome (PCOS) in which PCOS was induced by letrozole, orally in a dose of 1 mg/kg once daily for 3 weeks; and ADM group in which ADM was injected intraperitonally in a dose of 3.5/μg/twice daily for 4 weeks. At the end of the experimental period, the serum sex hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Intraovarian factors have regulatory roles during the entire process of follicular growth and play crucial roles in pathological conditions of the ovary, including PCOS 39,53,60,61 . We demonstrated for the first time that ER stress pathways are activated in the granulosa cells of both a mouse model of PCOS induced by the continuous administration of androgen and in humans, and this finding has been confirmed by other groups 48,62–67 . We also found that local hyperandrogenism in the follicular microenvironment of PCOS is an activator of ER stress in human granulosa cells, 52 and this finding has been confirmed in mouse granulosa cells 63 .…”
Section: Role Of Follicular Er Stress In the Pathophysiology Of Pcossupporting
confidence: 77%
“…Intraovarian factors have regulatory roles during the entire process of follicular growth and play crucial roles in pathological conditions of the ovary, including PCOS 39,53,60,61 . We demonstrated for the first time that ER stress pathways are activated in the granulosa cells of both a mouse model of PCOS induced by the continuous administration of androgen and in humans, and this finding has been confirmed by other groups 48,62–67 . We also found that local hyperandrogenism in the follicular microenvironment of PCOS is an activator of ER stress in human granulosa cells, 52 and this finding has been confirmed in mouse granulosa cells 63 .…”
Section: Role Of Follicular Er Stress In the Pathophysiology Of Pcossupporting
confidence: 77%
“…Similarly, Suetomi et al (2020) and Igarashi et al (2014) demonstrated the cytoprotective effect of ADM in pancreatic β-cells [ 24 ], as well as acute and chronic cerebral ischemia [ 35 ]. Accumulating evidence from previous research pointed to the antioxidant mechanism of ADM, which could be accredited to activating the PI3K/Akt pathway and mitigating ER stress [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, ADM co-treatment effectively reduced TNF-α, IL-1β, and IL-18 levels compared to their levels in the DOX-only treated group. The ADM-observed anti-inflammatory effect against DOX-induced nephrotoxicity could be accredited to the upregulation of PPAPγ, which has been found to be involved in anti-inflammatory reactions via TNF-α downregulation due to the suppression of ER stress [ 36 ]. These findings are consistent with previous studies by Li et al (2019) and Mahmoodazdeh et al (2020) [ 21 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggest that the intensive nursing of hyperglycemia optimization management can effectively improve the degree of nerve defect and the ability of daily living in patients with cerebral hemorrhage after operation. This is due to the optimal management of hyperglycemia intensive nursing inter-vention mode of patients with better blood glucose control can avoid hyperglycemia damage to neurons [27][28][29]. Hyperglycemia can increase the anaerobic metabolism of brain tissue, destroy mitochondria, produce a large number of free radicals, and increase the Ca2 + influx of nerve cells [30][31][32].…”
Section: Discussionmentioning
confidence: 99%